Following half-season intensive grazing on native pasture with alfalfa or sudangrass grazing and/or feedlot finishing - R.M. Helsel; Gerry L. Posler; Jack G. Riley; E.F. Smith; G.M. Ward (Kansas Agricultural Experiment Station Research Reports, 1978)
Late summer grazing of alfalfa or sudangrass by cattle coming off half-season, double-stocked native grazing showed no advantage over immediate feedlot finishing. Late-summer grazers gained less in the feedlot and required about the same feeding period as those animals taken to the feedlots in midsummer.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Alfalfa; Sudangrass; Feedlot finishing